2018
DOI: 10.3329/bjb.v44i4.38566
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variability, correlation and path coefficient analysis for yield and yield components in transplant aman rice (Oryza sativa L.)

Abstract: Analysis of variance revealed significant differences among the genotypes for all the traits. Flag leaf area (0.643**), productive tillers per plant (0.450**), 1000-grain weight (0.785**) and harvest index (0.920**) showed positive and strong significant association with grain yield per plant at genotypic level whereas plant height (–0.418*) and per cent spikelet sterility (–0.489**) possessed significant negative correlation with grain yield per plant. Flag leaf area (0.157) productive tillers per plant (0.48… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 9 publications
6
7
0
Order By: Relevance
“…Number of productive tillers per plant showed positive and moderate direct in MDU 6 × VGD1, whereas it was positive and high in ISM × VGD 1. The similar results were confirmed by Chhangte and Devi (2019) for moderate direct effect and by Roy et al, (2015) for high direct effect. The residual effect of the cross MDU 6 × VGD 1 is very high (0.887) implies that some other character also contributing towards the single plant yield apart from the characters under study.…”
Section: Resultssupporting
confidence: 85%
“…Number of productive tillers per plant showed positive and moderate direct in MDU 6 × VGD1, whereas it was positive and high in ISM × VGD 1. The similar results were confirmed by Chhangte and Devi (2019) for moderate direct effect and by Roy et al, (2015) for high direct effect. The residual effect of the cross MDU 6 × VGD 1 is very high (0.887) implies that some other character also contributing towards the single plant yield apart from the characters under study.…”
Section: Resultssupporting
confidence: 85%
“…Genetic variability for productive tiller per plant and number of grains per panicle was reported by Singh et al (2012). High heritability values in rice were also observed by Roy et al (2015). The high value of heritability for all the traits suggests that all these traits are under genetic control, i.e.…”
Section: Resultsmentioning
confidence: 87%
“…This indicated that the suppressive effect of the environment modified the phenotypic expression of these characters by reducing phenotypic correlation values. Roy et al (2015) also reported higher magnitude of genotypic correlation than respective phenotypic correlations between various characters in rice. Grain yield had significant positive correlation with effective tillers per hill (0.937**), panicle length (0.998**), filled grain per panicle (0.913**) and thousand grain weight (0.997**) and significant negative correlation with days to 50% flowering (−0.645**), days to maturity (−0.648**) and spikelet sterility (−0.862**).…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…Rajkumar and Ibrahim (2015) revealed that panicle exertion rate had positive association with out-crossing rate. Similarly Roy et al (2015) observed significant positive association between yield and its contributing traits in rice. Stigma exertion rate had the significant positive association with panicle exertion rate (0.995**), angle of florate opening (0.791**), duration of florate opening (0.963**), filament length (0.778**), stigma length (0.784**) and stigma breadth (0.764**) indicating high stigma exertion rate with high out crossing rate.…”
Section: Correlation Studiesmentioning
confidence: 80%